A Study on the Dependency Between Selected Global Stock Markets and Gold and Silver Futures - Ozan Kaymak (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
Globalization has enabled greater volume and frequency of economic and commercial practices to be implemented worldwide. As a result, with the expansion of the scope of capital expansion, the interdependence of financial markets increases. However, negative developments such as economic crises, epidemics, wars, and uncontrolled migrations cause the relations between markets to weaken and a significant number of investors to turn to commodity investments. This study aims to evaluate the validity of the Capital Asset Pricing Model (CAPM) theorem, which posits that the expected returns of financial assets are influenced by systematic and unsystematic risks within the context of the selected market data for the specified period. Specifically, the study seeks to analyze the potential cointegration and the effects of gold and silver futures returns on the returns of selected global stock markets using time-series analysis. The potential relationships between the monthly returns of selected global stock indices and the monthly returns of gold and silver futures were analyzed for the period from January 2014 to May 2024 using the Autoregressive Distributed Lag (ARDL) Bound Test method. By calculating the error correction coefficients, it has been determined how long it takes to restore the balance in case the balance between the stock markets and commodity markets is disrupted. As a result of the research, it was determined that there is a long-term cointegration relationship between gold and silver futures index returns and selected global stock index returns. In the case of a short-term imbalance in the relationship between the yields of selected global indices and the index returns of gold and silver-term transactions, the balance was recovered within 0.9042 months for the index return of gold-term operations and 0.6549 months for the index return of silver-term operations.